Correlation of cross-cut cylindrical heat sink to improve the orientation effect of LED light bulbs. (May 2015) - Jang, Daeseok; Kim, Dong Rip; Lee, Kwan-Soo
Abstract: We investigate cross-cut cylindrical heat sink to improve cooling of a light-emitting diode (LED) bulb compared with conventional plate-fin cylindrical heat sinks using various installation angles. In contrast to plate-fin heat sinks, whereby the fins in the upper heat sink do not provide effective cooling at large installation angles, flow formed between the cross-cut fins and the air reached the upper region of the heat sink. As the installation angle increased, the length of the flow path increased. Accordingly, the flow efficiency of the cooling air improved, and the dependence of the cooling on orientation was reduced. The improvement of the cross-cut heat sink was more noticeable in the shorter cross-cut length. We suggest a correlation to predict the degree of improvement in the thermal resistance compared with a plate-fin heat sink as a function of design parameters and installation angle, and develop a contour map describing the optimum heat sink shape for various installation angles.